ابي العباس القلقشندي: دراسة في سيرته - الحواني، شاكر مجيد كاظم; جبر، نداء خضير (جامعة البصرة ومركز البحث وتطوير الموارد البشرية رماح, 2020)
لا شك أن دراسة الشخصيات العلمية التي تركت أثرا في حياة الأمة تعد من الدراسات الضرورية؛ التي تسهم في فهم تاريخ الأمة، ومنجزها الحضاري، وما قدمته للبشرية عبر آثارها المعرفية المتنوعة، وموضوع بحثنا الذي يتعلق بحياة أبي العباس القلقشندي من هذه المواضيع المهمة، التي لابد من دراستها والتعريف بها، لاسيما انه أسهم في إنتاج مجموعة كبيرة من الكتب في مختلف العلوم السائدة في عصره؛ كالأدب والتاريخ والأنساب وغيرها، لازالت تحظى باهتمام الباحثين والدارسين لما تحمله من قيمة علمية كبيرة، لذلك حاولنا في هذا البحث قراءة حياته بصورة موجزة، ابتداء من ولادته وانتهاء بوفاته، مع التركيز على نشأته وبداياته العلمية وشيوخه والإجازات التي حصل عليها ثم ختمناه بالحديث عن الطلبة الذين تتلمذوا على يديه، فخرجنا بنتيجة مفادها أنه لم يكن مختصا بلون واحد من العلوم، فقد كان مؤرخا وأديبا وعالما بالنسب ومفتيا وحافظا، حتى صارت مؤلفاته مصادر مهمة لا يستغنى عنها أي باحث، فكان بحق كاتبا موسوعيا على درجة عالية من التميز، ومع هذا كله لم يحظ بالاهتمام المطلوب قديما أو حديثا، فمعظم من كتب عنه من معاصريه تناوله بترجمة مقتضبة لا تتناسب مع مكانته العلمية وأهمية مؤلفاته.
No doubt that the study of scientific characters which have made a difference in the course of the nation life are fairly deemed as significant studies which contribute in the understanding of the nation history , its cultural achievement and what it introduces for humanity across its various cognitive traces . The subject matter of our research which is related to Abu AL Abbas AL Qalqashandi's life is one of those important subjects which should be studied and introduced especially he took part in producing many books dealing with sciences prevailing at his era such as literature , history , genealogy and etc…. which have still attracted the interest of researchers and learners for the remarkable scientific value they reflect . Therefore , we attempted through this research to read his life briefly beginning from his birth to his death with focusing on his growth , scientific starts , elderly instructors and certificates he obtained and we finally concluded this research by talking about the scholars who were tutored by him . We have reached at a conclusion that he was not specialized in one aspect of science only . Yet , he was Historian , Man of letters , Scientist in genealogy, Mufti and Quran Hafiz to the extent that his works have become important sources and dispensable references for researchers that he is fairly an encyclopedic writer with high level of recognition . Despite his well – known and reputed track of achievements , he does not attract the worthiness he deserves whether in the past or present . Most of his contemporary writers who wrote about him , they introduced him through a brief translation which does not fit his own scientific position and the importance of his works .
Keywords: التاريخ القديم -- الجاهلية والإسلام -- الشخصيات التاريخية -- القلقشندي، أحمد بن علي بن أحمد، ت. 821 هـ